2006
DOI: 10.1177/102490790601300201
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Pulmonary Embolism in a Teenager: Case Report

Abstract: Massive pulmonary embolism is unusual in young people. We present a case of massive pulmonary embolism in a teenage Chinese patient. Initially he presented to the emergency department with dyspnoea and fever. Influenza B was diagnosed during his four-day stay in the paediatric ward. One week later he suddenly collapsed and presented to the emergency department with chest pain, syncope and dyspnoea. Despite undergoing rapid assessment, along with prompt admission to intensive care and cardiopulmonary resuscitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A case report by BayÕz et al 11 described a 38-year-old woman requiring thrombolysis following diagnosis of a pulmonary embolism, discovered to have both activated protein C resistance and protein S deficiency. Wong et al 12 outlined the case of a teenage boy readmitted with collapse and cardiac arrest following an initial diagnosis of influenza B virus. Postmortem revealed massive pulmonary emboli and thrombophilia studies showed protein C and protein S deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A case report by BayÕz et al 11 described a 38-year-old woman requiring thrombolysis following diagnosis of a pulmonary embolism, discovered to have both activated protein C resistance and protein S deficiency. Wong et al 12 outlined the case of a teenage boy readmitted with collapse and cardiac arrest following an initial diagnosis of influenza B virus. Postmortem revealed massive pulmonary emboli and thrombophilia studies showed protein C and protein S deficiency.…”
Section: Discussionmentioning
confidence: 99%